THE PARADIGM OF JUDGE'S THOUGHTS IN THE SETTLEMENT OF ISLAMIC INHERITANCE CASES AND THEIR IMPLICATIONS ON FAMILY LAW RENEWAL IN INDONESIA (Study on Supreme Court Decision Number 721 K/Ag/2015, Supreme Court Decision Number 218 K/Ag/2016, and Supreme Court Decision Number 331/K/AG/2018) - Pradikta, Hervin Yoki; Faisal, F.; Pane, Erina; Muafiah, Evi (SMART: Journal of Sharia, Traditon, and Modernity, 2021)
Judges do not only act as mouthpieces of the law and carry out normative and procedural laws and regulations, but also promote a sense of justice in the community. Several Supreme Court decisions such as Supreme Court Decision Number 721 K/Ag/2015, Supreme Court Decision Number 218 K/Ag/2016, and Supreme Court Decision Number 331/K/AG/2018, have illustrated the existence of progressive ijtihad that does not only adhere to positivistic legal reasoning but also to progressive legal reasoning by using the legal discovery method in the form of legal interpretation with a philosophical, empirical and juridical approach. In practice, the decisions mentioned above can be used as permanent jurisprudence by judges in all judicial bodies. The legal values contained in jurisprudence can be used as legal rules in upholding justice and legal certainty. The judge's decision has two important dimensions. First, the decision is a solution for solving Islamic inheritance cases for the disputing parties and outside the parties. Second, as a legal regulation for the future (ius constituendum). Keywords:     Judge's Decision, Ijtihad, Progressive, Jurisprudence.